The Use of DEA Method in Evaluating Credit Risks of Companies in Order to Obtain their Proper Credit Score - Feruś, Anna (Zastosowanie metody DEA do oceny ryzyka kredytowego przedsiębiorstw w ramach credit-scoringu, 2010)
Summary: The aim of the article is to present a new procedure of company credit risk forecast by using the DEA method under Polish economic conditions. The suggestion is strongly supported by the fact that so far the DEA method has not been applied to estimate credit risk of companies within the framework of credit-scoring. The research described in the article has been conducted on the basis of comparison of suggested DEA method with currently used procedures, namely point method, discriminative analysis and linear regression. Considering the research, it can be concluded that DEA method facilitates forecasting financial problems, including the bankruptcy of companies in Polish economic conditions, and its effectiveness is comparable or even greater than approaches implemented so far.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 98, s. 62-70
Keywords: credit scoring; credit risk; Data Envelopment Analysis; technical efficiency; creditworthiness